PELATIHAN SOLUSI INOVATIF UNTUK MENINGKATKAN KEMAMPUAN MENULIS ARTIKEL ILMIAH MELALUI PENDEKATAN ARTIFICIAL INTELEGENSI (AI) - Ritonga, Wahyu Azhar; Aditiya, Rahmad; Syafriyeti, Rahmi; Megawati, Betti; Ritonga, Maisaroh; Nursalimah (Fakultas Ilmu Komputer, 2025)
Scientific article writing training is an essential skill for students and academics in conveying their research findings and scientific thinking. However, various challenges such as limited academic vocabulary, writing structure, and time often become obstacles. This study aims to develop effective writing strategies and evaluate Artificial Intelligence (AI)-based training as an innovative solution to improve the quality and productivity of scientific article writing skills and understand the ethics of using AI in academic writing. The method used was a quasi-experimental model with a structured training model, utilizing AI-based tools such as ChatGPT, Grammarly, and SciSpace. The results showed a significant increase in the quality and productivity of the training participants' writing. This training provides evidence that an AI approach can be an effective tool in academic literacy.